Productivity Analysis of Gillnet Fishermen Business at the Fishing Port of Archipelago Pemangkat - Lamsah, Lamsah; Merdekawati, Dewi; Muslimah, Muslimah (PAKIS JOURNAL INSTITUTE, 2024)
Pemangkat Archipelago Fisheries Port (PPN) has a very strategic role in the development of capture fisheries business, namely as a center or center for marine fisheries activities, especially those in the Sambas Regency, West Kalimantan Province. The purpose of this study was to determine the productivity level of gillnet fishing gear and to determine the factors that affect gillnet catches. The method used in this research is descriptive method. Based on the results of the analysis using the Cobb Douglas model, the production factor that affects the catch using gillnet fishing gear is the distance traveled with a value of Tcount 2,168 < Ttable 2,048. The highest productivity of catch units on gillnet fishing gear, which is 8 tons/trip, is found on the Sri Ayu Bahari vessel with a 29 GT vessel size, while the lowest is 1,3 tons/trip on the Sumber Abadi – 3 vessel with a 30 GT vessel size. Considering that the gillnet catching business is still profitable, the Pemangkat Fisheries Port can still develop its business with this tool, but it is necessary to control the PPN so that the catches obtained by gillnet fishermen remain optimal.